Ureteral Complications after Pediatric Kidney Transplantation: Observations in 84 Patients at Santa Casa of São Paulo - Guidoni, Luiz Renato Montez (2005)
Introduction: The main ureteral complications after kidney transplantation are urinary leakage, stenosis and reflux, varying from 2 to 10%. In general, these complications do not cause the graft loss or fatal outcome. Purpose: Analyze the ureteral complications in kidney transplanted children in a single institution, and relating patient to graft survival. Methods: A transversal retrospective study with 84 consecutive pediatric kidney recipients at Santa Casa de São Paulo, performed between 1985 and 2005 (ages ranged from 1 to 17 years old) was conduced. Results: From an amount of 84 patients, 9 presented ureteral complications (10.7%), being 8 cases of urinary leakage (9.5%), and 1 ureteral stenosis (1.1%). All the urinary leakage occurred between the second and thirty-sixth postoperative day (mean 11 days). There was no vesicoureteral reflux case reported. Only two patients (1.7%) presented graft dysfunction developed during the first postoperative year. Conclusion: The ureteral complications led to little morbidity in terms of graft dysfunction and patient survival.